Performance Analysis of the Public Safety Center (PSC) Building Construction Project in Probolinggo Regency - Lucky Hendra Saputra; Andi Patriadi; Sajiyo Sajiyo (Syntax Corporation Indonesia, 2025)
The construction of the Public Safety Center (PSC) building in Probolinggo District represents a significant government initiative aimed at enhancing health emergency response services. This project, like many others, encountered various challenges, particularly concerning cost, time, and quality management. To assess the project’s performance, this study applies the Earned Value Analysis (EVA) method, which is widely used for monitoring and controlling project performance. The key data used for this analysis includes the Actual Cost of Work Performed (ACWP), Budgeted Cost of Work Performed (BCWP), and Budgeted Cost of Work Scheduled (BCWS), which together provide a comprehensive overview of both cost and schedule performance. The study reveals several critical findings, including periods where the project faced significant budget and time overruns, as well as where performance was optimized. Based on these findings, strategic recommendations are proposed to improve project control and ensure that future PSC development projects are more effective and efficient. By providing actionable insights, this research aims to serve as a valuable reference for stakeholders involved in similar infrastructure projects, offering guidance on how to better manage and control cost and schedule, mitigate risks, and achieve desired project outcomes